REDUCTION OF TOXIC ELEMENT MOBILITY IN MINING SOIL BY ZEOLITIC AMENDMENTS - Giannatou, S.; Vasilatos, Ch.; Mitsis, I.; Koukouzas, N.; Itskos, G.; Stamatakis, G.M. (Bulletin of the Geological Society of Greece, 2016)
The aim of this study is to examine the effectiveness of natural and synthetic zeolitic materials as potential amendments for the rehabilitation of mine degraded areas. Two types of natural zeolite tuffs, clinoptilolite- and mordenite rich originating from Samos Island, Greece, were used as low cost modifiers. In addition, the synthetic zeolite Na-P1, produced from lignite fly ash of the Meliti Lignite fired Power Station (Florina, Greece), was used. Fly ash was converted into synthetic zeolite via a low temperature alkaline hydrothermal treatment. In order to evaluate the aquatic solubility and potential bioavailability of heavy metals in contaminated soils of the mining area of Lavrion, specific soil amendments were used in leaching experiments. The Na-P1zeolite proved to be the most effective among the tested amendments for in situ de-contamination of mining soils. Comparing the two natural zeolites used, the mordenite-rich tuff exhibited better results than the clinoptilolite-rich, for the reduction of the potential bioavailability of almost all the studied heavy metals. Despite the high trace element content of the specific soils, it was observed that the Glaucium flavum, a plant that grows in the contaminated soils of Lavrion, does not accumulate high concentrations of metals; therefore the high toxic element content of soils does not always influence the physiology of the plants.